Two case reports of fetal alcohol syndrome: broadening into the spectrum of cardiac disease to personalize and to improve clinical assessment - R. Onesimo; C. De Rose; A. B. Delogu; A. Battista; C. Leoni; S. Veltri; G. De Rosa; G. Zampino (BMC, 2019)
Abstract Background Fetal alcohol spectrum disorder (FASD) refers to a broad spectrum of disabilities, in infants and children, resulting from moderate to excessive prenatal alcohol exposure. Significant associations with alcohol exposure were already reported with congenital structural heart defects: i.e. ventricular septal defects, atrial septal defects, conotruncal defects. Cases presentation We describe two cases of children with FASD, both admitted to the Center for Rare Diseases and Birth Defects of Policlinico Universitario Agostino Gemelli, in whom asymptomatic cardiac rhythm alterations were detected in absence of structural cardiovascular system anomalies or cardiac channelopathies. Conclusions No other reports about cardiac rhythm anomalies in individuals affected by FASD are actually available from the literature. We would like to make an alert for clinician, given the possibility of finding anomalies of heart conduction and rhythm in children affected by FASD even without structural congenital heart disease.